Impact regimes of a single water droplet impacting a hot immiscible liquid surface - Xu, Mingjun (2024)
This paper studied the dynamic interaction process of a single water droplet impinging onto an immiscible target liquid, which was a follow-up study on a single water droplet impacting a miscible target liquid i.e. ethanol. Heptane was chosen as the impacted liquid, and the water droplet with a fixed diameter of 1.98 mm was used in the experiments. The droplet Weber number ranged from 30 to 762 by changing the height between the droplet and the impacted liquid surface. A high-speed digital camera at a speed of 2000 fps was used to capture the dynamic process. A comprehensive map We∼θ of typical impact phenomena including penetration, splashing, and bubble was plotted, considering both the cases of immiscible and miscible liquids. The critical Weber numbers of forming the typical phenomena were deduced. The critical Weber numbers for the transition from penetration to splashing and the transition from splashing to bubble could be approximately predicted by We=824.3−140.9e1.5θ and We=62.1+61.5θ, respectively. To clarify the formation mechanisms of typical phenomena, the energy conversions during the dynamic process were analyzed. The influences of pool temperature on energy conversion rates of the crater and jet formation could be predicted by χ=0.437θ+0.156 and φ=0.245θ+0.072, respectively.